Temporal Analysis of the Influence of the Number of Vaccinations on the Number of Covid-19 Cases in South Sulawesi Province Using ARIMAX Model - Aswi Aswi; Muhammad Arif Tiro; Sudarmin Sudarmin; Ruliana Ruliana; Andi Gagah Palarungi Taufik; Zulhijrah Zulhijrah (Indonesian Journal of Fundamental Sciences, 2022)
South Sulawesi is a province that has the highest number of Covid-19 cases in the Sulawesi island region. Vaccination is one way that is considered effective in controlling the infection of a disease. Covid-19 vaccination in Indonesia was carried out in January 2021. This study aims to obtain the best Autoregressive Integrated Moving Average X (ARIMAX) model in modeling the effect of the number of vaccinations on the number of Covid-19 cases in South Sulawesi Province. Data on the number of vaccinations and Covid-19 cases in South Sulawesi Province (October 1, 2021 - January 31, 2022) were used. The best ARIMAX model in modeling Covid-19 in relation to the number of vaccinations is ARIMAX (2,1,0). The results showed that the number of vaccinations had a negative effect on the number of Covid-19 cases at the significant level of 10%. This indicates that if the number of vaccinations increases then the number of Covid-19 cases will decrease.